2005
DOI: 10.1080/13607860412331336760
|View full text |Cite
|
Sign up to set email alerts
|

Attachment behaviours and parent fixation in people with dementia: The role of cognitive functioning and pre-morbid attachment style

Abstract: This study replicates and extends exploratory research into the occurrence of attachment behaviours and parent fixation amongst people with dementia. Relationships between cognitive functioning, pre-morbid attachment style, attachment behaviours and parent fixation were examined. Fifty-three people with dementia, living in residential or nursing homes, completed the Standardised Mini-Mental State Examination and were interviewed about their parents. A family member or friend rated pre-morbid attachment style a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 19 publications
2
43
2
Order By: Relevance
“…On this basis he suggested that progressive short-term memory failure causes people to become disorientated to their surroundings, and also to the presence of, and emotional response from, attachment figures (Miesen & Jones, 1997). As a consequence, overt attachment behaviours become less useful and symbolic attachment (Cicirelli, 1991), in the form of thinking about the parents as if they were still alive, provides the person with a sense of emotional security (Browne & Schlosberg, 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…On this basis he suggested that progressive short-term memory failure causes people to become disorientated to their surroundings, and also to the presence of, and emotional response from, attachment figures (Miesen & Jones, 1997). As a consequence, overt attachment behaviours become less useful and symbolic attachment (Cicirelli, 1991), in the form of thinking about the parents as if they were still alive, provides the person with a sense of emotional security (Browne & Schlosberg, 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…More recently, Browne and Schlosberg (2005) hypothesized that invoking the presence of parents may not be as comforting for all individuals as it would depend on their pre-morbid attachment style (anxious-ambivalent, avoidant or secure). Their study showed support for Miesen's (1993) finding that parent fixation was associated with individuals with lower levels of cognitive functioning.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Winnicott's theory of transitional objects suggests that children form attachments with objects that offer security and comfort as they transition through individuation. 16 Inverse parallels have been drawn between the development of people in later stages of dementia and early childhood development. This move is intended not to infantilize or to ignore their wealth of life experiences, but to provide a framework to comprehend the normal attachment to objects and the relevance of transitional objects throughout the lifespan.…”
Section: Introductionmentioning
confidence: 99%